Prevalence and Risk Factors of Post-Traumatic Stress Disorder Among Emergency Medicine Trainee Doctors in Sudan Medical Specialization Board - Mohamed, Ahmed; Elshafei, Abla Mohamed Elmahdi; Alteib, Mogahid Alteib Yousif (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Post-traumatic stress disorder (PTSD) is a mental health condition triggered by traumatic events. Emergency medicine (EM) trainees, frequently exposed to severe injuries, death, and high-pressure situations, are highly vulnerable. Research on PTSD prevalence and contributing factors among EM trainees in resource-limited settings like Sudan is scarce. This study aimed to assess the prevalence of PTSD symptoms among EM trainees in the Sudan Medical Specialization Board (SMSB) and identify contributing factors. Methodology: A cross-sectional analytic study was conducted from July 24 to September 18, 2020. A total of 171 SMSB EM trainees (response rate: 75%) completed a self-administered PTSD Checklist (PCL-C, civilian version) through an online questionnaire distributed via social media. The PCL-C measured the severity of PTSD symptoms across various clusters. Data were analyzed using SPSS version 26, employing descriptive statistics and chi-square tests to assess associations between PTSD symptoms and sociodemographic or work-related factors. Results: The prevalence of severe PTSD symptoms among trainees was 35.1%, with 33.9% experiencing moderate-to-severe symptoms. Numbness was the most common symptom cluster, reported by 47.1% of trainees. Key risk factors included being female, unmarried, under 32 years old, in the first or second year of training, and working in military hospitals. Trainees previously diagnosed with mental illness exhibited higher PTSD symptom severity (2.9%). The most frequently reported traumatic event was witnessing a patient’s death after unsuccessful resuscitation (28.2%). High-severity PTSD symptoms were predominantly associated with witnessing medical complications leading to disability (54.3%). Conclusion: The study revealed a concerning prevalence of PTSD among EM trainees, emphasizing the need for proactive interventions, including mental health evaluation, counselling, and resilience training. Future research should focus on identifying additional risk factors and evaluating the role of social and occupational support systems in mitigating PTSD in medical trainees.